Unveiling the mind of Kenyan undergraduates : motives for abortion - (:unkn) unknown (My University, 2015)
Abortion has become a highly volatile moral issue in which neutrality proves almost impossible (Novak, 1993). Looking back in time, the concept proves itself not uncommon even to the most primitive societies where feticide for instance, was considered one of the ‘abominations of Egypt’ (Bleich, 1968). For the Kenyan context, this is reflected in what has been termed as ‘female crimes’ whereby abortion accounts for 84% of these crimes by young women aged 16 – 25 years (Njonjo, 2010). With such statistics, it is quite clear why this topic is heavily studied and researched on. It must be highlighted though, that people’s views on abortion reflect their beliefs on fundamentally important issues such as when life begins, when the rights of the fetus become equal to the rights of the mother and whether or not we have complete sovereignty over our own bodies (Gleeson, Forde, Bates, Powell, Jones & Draper, 2008).
9TH Annual ethics conference. Theme : Bioethics medical, legal, environmental and cultural aspects in healthcare ethics at STRATHMORE UNIVERSITY, 25-26 OCTOBER 2012.
Abortion has become a highly volatile moral issue in which neutrality proves almost impossible (Novak, 1993). Looking back in time, the concept proves itself not uncommon even to the most primitive societies where feticide for instance, was considered one of the ‘abominations of Egypt’ (Bleich, 1968). For the Kenyan context, this is reflected in what has been termed as ‘female crimes’ whereby abortion accounts for 84% of these crimes by young women aged 16 – 25 years (Njonjo, 2010). With such statistics, it is quite clear why this topic is heavily studied and researched on. It must be highlighted though, that people’s views on abortion reflect their beliefs on fundamentally important issues such as when life begins, when the rights of the fetus become equal to the rights of the mother and whether or not we have complete sovereignty over our own bodies (Gleeson, Forde, Bates, Powell, Jones & Draper, 2008).